A bibliometric review of inclusive governance concept - Nasrun Annahar; Ida Widianingsih; Caroline Paskarina; Entang Adhy Muhtar (Cogent Social Sciences)
This study aims to analyze the growth trajectory of global scientific output on the “inclusive governance” concept, and governance principles that have received the most attention. The bibliometric review was used in this study on the Scopus database. The data were analyzed using VOSviewer 1.6.16 version and Microsoft Excel. This review found that the term “inclusive governance” was first used in 2000 and has continued to increase significantly since 2013. This review found that the authors of inclusive governance emphasized more on principles: participation, power, accessibility, structure, accountability, empowerment, fairness, collaboration, capacity, and decision-making. This review provides a new and beneficial way to reveal the history of the inception of inclusive governance thinking as a derivative of the grand paradigm of governance, along with the principles that were emphasized by previous authors.